Research of the Energy Match Optimization for Range-extended Hybrid Powertrain - Ye Xin; Ye Ming; Luo Yong; Ma Yaya; Li Kuankuan (Jixie chuandong)
On the basis of the dynamics analysis of range-extended hybrid electric vehicle,under the particular condition,taking the most efficient of system as optimization object,the rule of mode shifting of range-extended hybrid electric vehicle is built.Based upon with the MATLAB/Simulink simulation platform,the simulation model is established,the simulation results show that the vehicle economy fuel and dynamics are both boosted by this energy management strategy.The test rig of hybrid system based upon the Matlab/Simulink Simulation platform and dSPACE hardware-in-the-loop is set up.And the data acquisition and control system is developed.The energy management control strategy of RE-HEV at particular drive cycle is validated by experiments.